What Freud didn't know : a three-step practice for emotional well-being through neuroscience and psychology - Stokes, Timothy B., 1948- (Rutgers University Press, 2009)
What Freud Didn't Know, well-supported by research and groundbreaking in theory, combines neuroscience and psychology to explain how the amygdala region of the brain evolved to unconsciously record, store, and activate emotional memory loops and imagery associated with painful events, especially those of childhood. This book is the first to bring together diverse, post-Freudian discoveries to produce a coherent three-step practice for understanding problematic aspects of the human mind which can be mastered easily, in a clinical or self-help setting. Timothy B. Stokes explores recent breakthro.